2008
DOI: 10.1681/asn.2007090970
|View full text |Cite
|
Sign up to set email alerts
|

Role of Remission Clinics in the Longitudinal Treatment of CKD

Abstract: Heavy proteinuria is a major determinant of progression to ESRD for patients with chronic nephropathies and reducing proteinuria should be a key target for renoprotective therapy. In the Remission Clinic, we applied a multimodal intervention to target urinary proteins in 56 consecutive patients who had Ͼ3 g proteinuria/d despite angiotensin-converting enzyme inhibitor therapy. We compared the rate of GFR decline and incidence of ESRD in this cohort with 56 matched historical reference subjects who had received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 52 publications
9
146
1
2
Order By: Relevance
“…[1][2][3][4] These findings imply that urinary proteins should be reduced as far as possible, ideally to ,1 g/d. 5 Inhibitors of the renin-angiotensin system (RAS), such as angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs), are the antihypertensive drugs that most effectively reduce urinary proteins and slow GFR decline in patients with CKD. 1-3, 6 The efficacy of treatment, however, is heterogeneous and dependent on inborn 7 and environmental [8][9][10][11][12] factors.…”
mentioning
confidence: 99%
“…[1][2][3][4] These findings imply that urinary proteins should be reduced as far as possible, ideally to ,1 g/d. 5 Inhibitors of the renin-angiotensin system (RAS), such as angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs), are the antihypertensive drugs that most effectively reduce urinary proteins and slow GFR decline in patients with CKD. 1-3, 6 The efficacy of treatment, however, is heterogeneous and dependent on inborn 7 and environmental [8][9][10][11][12] factors.…”
mentioning
confidence: 99%
“…This was demonstrated effectively by a multimodal intervention strategy, the Remission Clinic program, that used all available lifestyle recommendations and pharmacologic tools to further reduce proteinuria in patients with CKD and severe proteinuria already treated with RAAS-blocking agents. [46][47] We recently confirmed the beneficial effects of this strategy in patients with Alport syndrome. 48…”
Section: Proteinuria: the Second "P" For Ckd Progressionmentioning
confidence: 60%
“…[12][13][14] The prevalent CKD etiology was hypertensive nephrosclerosis (29%), followed by DKD (17%) and chronic glomerulonephritis (16%), which are related to the main causes of CKD in patients who underwent HD in Brazil. 3 Sesso et al and Fernandes et al showed that most patients who start on RRT in our country is referred to nephrology services very late, and most are on stage 4 (47.3%), which contrasts with data in international literature, in which most patients are on stage 3.…”
Section: Discussionmentioning
confidence: 99%
“…3 Sesso et al and Fernandes et al showed that most patients who start on RRT in our country is referred to nephrology services very late, and most are on stage 4 (47.3%), which contrasts with data in international literature, in which most patients are on stage 3. [3][4][5][6][7][8][9][10][11][12][13][14][15] Besides the expected contribution of age and CKD staging, the correlation of proteinuria with the progression of the renal disease, even if eased by the renoprotection by ACEI and ARB, is demonstrated in many studies. [16][17][18] This phenomenon is clearly observed in patients with type II DM, in which ¼ of the patients presents with renal compromise after ten years of disease.…”
Section: Discussionmentioning
confidence: 99%